LINGUOCULTURAL MODEL AND EDUCATIONAL FUNCTION OF THE CATEGORY OF "RESPECT" IN ENGLISH AND UZBEKISTAN FAIRY TALES - Eshankulova Saida Saydaliyevna; Egamberdiyeva Shag’zoda Damirovna (Bright Mind Publishing, 2026)
This scientific article examines the linguistic and cultural model of the category of “respect” in English and Uzbek fairy tales and its educational function based on a comparative analysis. In the study, the concept of respect is interpreted not only as a linguistic phenomenon, but also as a mechanism that shapes cultural experience and social behavior. By analyzing fairy tale texts, the author pays attention to the issues of how respect is transformed into a value through language, how it is naturalized as a social norm, and how it forms an educational model in the reader’s mind. The article reveals the transmission of the category of respect in English and Uzbek fairy tales through cultural codes, symbolic signs, and speech forms, and discusses the pedagogical significance of this process. The results of the study show that the category of respect in fairy tale discourse reflects the inextricable link between language, culture, and education.
Keywords: Category of respect, linguistic and cultural, fairy tale discourse, educational function, values, English fairy tales, Uzbek fairy tales.